Paresthesia frequency in fibromyalgia and its effects on personality traits. (2nd July 2018) - Balbaloglu, Ozlem; Tanik, Nermin; Alpayci, Mahmut; Ak, Hakan; Karaahmet, Elif; Inan, Levent Ertugrul
Abstract: Aim: Paresthesia and personality disorders are common conditions among patients with fibromyalgia. However, no previous study has examined a possible relation of paresthesia with personality traits in fibromyalgia. This study investigates the frequency of paresthesia in fibromyalgia patients and its relation with personality traits. Method: Female patients with fibromyalgia ( n  =   101) were divided into two groups according to the presence ( n  =   49; mean age 40.63 ± 7.62 years; range 23–55 years) or absence ( n  =   52; mean age 40.50 ± 7.12 years; range 27–53 years) of paresthesia. Also, a healthy control group ( n  =   53; mean age 39.34 ± 5.26 years; range 23–55 years) was included. The groups were evaluated by the Temperament and Character Inventory. Accordingly, temperament includes four dimensions: harm avoidance, novelty seeking, persistence, reward dependence; and character consists of three dimensions: cooperativeness, self‐transcendence, self‐directedness. Results: There were no significant differences among the three groups in the scores of novelty seeking, persistence, reward dependence and cooperativeness (for all P  >   0.05). Both fibromyalgia groups had significantly higher scores in harm avoidance and had lower scores in self‐directedness compared to the control group ( P  <   0.001). Also, fibromyalgia patients with paresthesia had significantly higher harm avoidance and self‐directedness scores than those in patients without paresthesia ( P  <   0.001). In both fibromyalgia groups, self‐transcendence scores were similar ( P  =   0.465) but significantly higher than in the control group ( P  <   0.001). Conclusion: This is the first study evaluating the association of paresthesia and personality traits in fibromyalgia. These results suggest that psychological distress associated with high harm avoidance and low self‐directedness scores are more prominent in fibromyalgia patients, and especially of those who have paresthesia.